Pengaruh Model Pembelajaran Kooperatif Tipe Connecting, Organizing, Reflecting, Extending Terhadap Kemampuan Pemecahan Masalah Matematika Siswa SMP - Aryska Putri R.Y, Risky; Fitri, Haida; Aniswita, Aniswita; Imamuddin, M. (EDUSAINS : Journal of Education and Science, 2023)
The background of this research is the low ability to solve mathematical problems in class VIII students of SMPN 1 IV Koto, Banuhampu District, Agam Regency, West Sumatra Province. The purpose of this study was to determine whether there was an influence of the Connecting, Organizing, Reflecting, Extending (CORE) cooperative learning model on students' mathematical problem solving abilities. This type of research is pre-experimental with a static group comparison design. The sampling technique is taken randomly. The sample in this study were students of class VIII.4 as the experimental class and class VIII.2 as the control class. The instrument used is a test of mathematical problem solving abilities. The results of solving students' math problems are calculated using the t-test. The research results obtained tcount = 3.83 and ttable = 1.68 because tcount > t table e means H0 is rejected. So it can be concluded that there is an influence of the Connecting, Organizing, Reflecting, Extending (CORE) cooperative learning model on the mathematical problem solving abilities of class VIII students of SMPN 1 IV Koto. Abstrak Penelitian ini dilatarbelakangi oleh rendahnya kemampuan pemecahan masalah matematika di kelas VIII SMP Negeri 1 IV Koto, Kecamatan Banuhampu, Kabupaten Agam, Provinsi Sumatera Barat. Tujuan penelitian ini yaitu untuk mengetahui apakah terdapat pengaruh model pembelajaran kooperatif tipe Connecting, Organizing, Reflecting, Extending (CORE) terhadap kemampuan pemecahan masalah matematika siswa. Jenis penelitian  ini adalah pra eksperimen dengan rancangan penelitian the static group comparison design. Teknik pengambilan sampel diambil secara random. Sampel dalam penelitian adalah siswa kelas VIII.4 sebagai kelas eksperimen dan kelas VIII.2 sebagai kelas kontrol. Instrumen yang digunakan adalah tes kemampuan pemecahan masalah matematika. Hasil pemecahan masalah matematika siswa dihitung dengan menggunakan uji-t. Hasil penelitian diperoleh thitung = 3,83 dan ttabel = 1,68 karena thitung > ttabel berarti H0 ditolak. Sehingga dapat disimpulkan bahwa terdapat pengaruh model pembelajaran kooperatif tipe Connecting, Organizing, Reflecting, Extending (CORE) terhadap kemampuan pemecahan masalah matematika siswa kelas VIII SMP Negeri 1 IV Koto.